Default risk and cross section of returns - Nusret Cakici; Sris Chatterjee; Ren-Raw Chen (Journal of Risk and Financial Management, 2019)
Prior research uses the basic one-period European call-option pricing model to compute default measures for individual firms and concludes that both the size and book-to-market effects are related to default risk. For example, small firms earn higher return than big firms only if they have higher default risk and value stocks earn higher returns than growth stocks if their default risk is high. In this paper we use a more advanced compound option pricing model for the computation of default risk and provide a more exhaustive test of stock returns using univariate and double-sorted portfolios. The results show that long/short hedge portfolios based on Geske measures of default risk produce significantly larger return differentials than Merton's measure of default risk. The paper provides new evidence that mediates between the rational and behavioral explanations of value premium.
Keywords: 330; risk management; default risk; option pricing